DIGITALISASI PELAYANAN KESEHATAN DAN IMPLIKASINYA TERHADAP HUKUM ADMINISTRASI: STUDI LITERATUR TENTANG PEMANFAATAN TEKNOLOGI DAN PERAN REGULASI - Jackson Yumame (ADMIN: Jurnal Administrasi Negara, 2025)
The digitisation of healthcare services is one of the most important developments in modern healthcare. The use of technologies such as telemedicine, electronic medical record systems, and health apps has brought about significant changes in the way services are provided to the public. The results of this study indicate that digitisation offers significant benefits in terms of efficiency, accessibility, and improved service quality. However, the legal implications that arise require special attention, particularly in terms of privacy protection, system security, and ensuring inclusivity for vulnerable groups affected by the digital divide. Adaptive and responsive regulations are key to maintaining a balance between technological innovation and public interests. Therefore, this study emphasises the importance of collaboration among various parties—government, healthcare providers, and the public—to ensure the success of digitalisation in meeting the need for better healthcare services. With the right regulatory approach, digitalisation of healthcare services can be a solution that not only supports technological advancement but also ensures justice and legal protection for all parties.